Mechanism of Copper (I)-catalyzed cycloaddition of azides to Terminal Alkynes: A quantum mechanical investigation (Latakia University Journal -Basic Sciences Series, 2023)
In this work, the mechanism for copper-catalyzed alkyne-azide cycloaddition (CuAAC) of benzyl-azide to Phenyl-acetylene was studied by quantum mechanical calculations. Clarification of the reaction mechanism will enable more control over the synthesis process and help to obtain tailor-made products in good yields with copper-catalyzed. The feasibility of the experimentally proposed reaction mechanism was investigated by modeling the profound intermediates and the transition state structures connecting them. The efficient theory level for the investigation of a click reaction is one of the main questions considered in quantum mechanical studies.The DFT calculations with MN12-L functional with both basis sets Def2-TZVP for Cu and Def2-SVP for other elements, combination herein shows that the cycloaddition process of the proposed copper acetylide structures with azide requires facile energies within the proposed paths to triazole synthesis. The number of metal atoms involved in the click reaction is taken into consideration. In CuAAC reaction, a comparison of mononuclear and dinuclear paths shows that the barrier for mononuclear cases is lower than that of dinuclear for (HCN, NHC, PPh3) Ligands.